The silent hour [videorecording (DVD)] - Hall, Dan; Kinnaman, Joel; Phifer, Mekhi; Strong, Mark (Paramount, 2024)
Follows a hearing-impaired police detective who works as an interpreter for the department and must confront a team of corrupt cops trying to eliminate a deaf murder witness in an apartment building.